Neonatal Tract-Based Spatial Statistics Findings and Outcome in Preterm Infants - van Kooij, B.J.M.; de Vries, L.S.; Ball, G.; van Haastert, I.C.; Benders, M.J.N.L.; Groenendaal, F.; Counsell, S.J. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: WM injury is associated with different disabilities that children born prematurely may experience during their lives. The aim of this study was to use TBSS to test the hypothesis that WM microstructure at TEA in preterm infants is correlated with cognitive and motor outcome at 2-year corrected age. MATERIALS AND METHODS: Sixty-three preterm infants, born at a mean gestational age of 28.7 weeks, underwent MR imaging and DTI at TEA. Neurodevelopmental performance was assessed by using the BSITD-III. Voxelwise analysis of the DTI data was performed by using TBSS to assess the relationship among FA, AD, and RD at TEA, and cognitive, fine-motor, and gross-motor scores at 2-year corrected age. RESULTS: Cognitive scores were correlated with FA values in the CC. Fine-motor scores were correlated with FA and RD throughout the WM. Gross-motor scores were associated with RD in the CC, fornix, and internal and external capsule. CONCLUSIONS: WM microstructure in preterm infants at TEA was associated with cognitive, fine-motor, and gross-motor performance at 2-year corrected age. This study suggests that TBSS of DTI data at TEA has the potential to be used as a biomarker for subsequent neurodevelopment. ADaxial diffusionBSITD-IIIBayley Scales of Infant and Toddler Development, Third editionCCcorpus callosumFAfractional anisotropyFMRIBFunctional MR Imaging of the BrainPLICposterior limb of the internal capsuleRDradial diffusionTBSStract-based spatial statisticsTEAterm-equivalent ageTFCEthreshold-free cluster enhancement